Characteristic Effects of Anti-dementia Drugs on Rat Sleep Patterns - Takayuki Ishida; Chiaki Kamei (Elsevier, 2009)
The present study was undertaken to clarify the effects of anti-dementia drugs on sleep pattern in rats. Electrodes were chronically implanted into the frontal cortex and the dorsal neck muscle of rats for the electroencephalogram (EEG) and electromyogram (EMG), respectively. EEG and EMG were recorded with an electroencephalograph. SleepSigh ver. 2.0 was used for analysis of the sleep-wake state. Total times of waking, non-rapid eye movement (non-REM) sleep, and rapid eye movement (REM) sleep were measured from 10:30 to 16:30. Galantamine had no significant influence on the sleep pattern. On the other hand, donepezil and memantine showed significant increases in sleep latency and total waking time and a decrease in total non-REM sleep time. Furthermore, memantine decreased total REM sleep time. To investigate the characteristics of non-REM sleep in detail, non-REM sleep was classified as stage 1, 2, or 3 according to the depth of sleep. Different from donepezil and galantamine, memantine significantly decreased stage 1 and increased stage 3 in non-REM sleep. From these findings, it can be concluded that galantamine caused no sleep disturbance, different from donepezil and memantine. Keywords:: donepezil, galantamine, memantine, sleep-wake pattern, dementia